2009
DOI: 10.1017/s0144686x08008349
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequality in health among elderly people in a combined framework of socioeconomic position, family characteristics and social support

Abstract: This study analyses gender inequalities in health among elderly people in Catalonia (Spain) by adopting a conceptual framework that globally considers three dimensions of health determinants : socio-economic position, family characteristics and social support. Data came from the 2006 Catalonian Health Survey. For the purposes of this study a sub-sample of people aged 65-85 years with no paid job was selected (1,113 men and 1,484 women). The health outcomes analysed were self-perceived health status, poor menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 73 publications
2
21
1
6
Order By: Relevance
“…Educated women (albeit primary education) have a different psychological health status, compared with older women who receive no schooling. The present findings are consistent with a study on the elderly, which used Limiting Long-standing Illness (LLI) as a health indicator (8). This study was conducted in Spain and the researchers reported the following: "Low educational attainment was not significantly associated with LLI among men, whilst a positive relationship with a gradient was found for women."…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Educated women (albeit primary education) have a different psychological health status, compared with older women who receive no schooling. The present findings are consistent with a study on the elderly, which used Limiting Long-standing Illness (LLI) as a health indicator (8). This study was conducted in Spain and the researchers reported the following: "Low educational attainment was not significantly associated with LLI among men, whilst a positive relationship with a gradient was found for women."…”
Section: Discussionsupporting
confidence: 80%
“…Older women in Singapore also had a poorer health status (self-reported health, chronic illness, and functional disability) in comparison with older men (14). Apparently, gender inequalities in health among the elderly in Asia are similar to Western countries, eg, Sweden, Spain, and Italy (7,8,15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research on the social determinants of health among older people has only recently started integrating different approaches that previously tended to be studied separately: socioeconomic position, family characteristics, and social support [25]. The study’s overall aim is to assess the interplay between social network satisfaction, socioeconomic position, and SRH among elderly men and women in European countries with different welfare regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Chia et al (2004) investigated the impact of visual impairment on HRQoL in an older population. There was also a study conducted by Rueda and Artazcoz (2009) where gender inequalities of health status among elderly people were measured. Relationships between elder people and income were studied by Huguet, et al (2008).…”
Section: Hrqol Among Elderlymentioning
confidence: 99%